2015
DOI: 10.1007/s11801-015-4127-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of temperature and refractive index based on a core-offset Mach-Zehnder interferometer cascaded with a long-period fiber grating

Abstract: An all-fiber sensor based on a cascaded optical fiber device is proposed and demonstrated, and its sensor head is composed of a core-offset Mach-Zehnder interferometer (MZI) and a long-period fiber grating (LPFG). In the experiment, two dips shaped by the intermodulation between the interference fringe of MZI and the resonant wavelength of LPFG are monitored. Experimental results show that temperature sensitivities of two dips are 0.060 7 nm/°C and 0.056 3 pm/°C, and the refractive index (RI) sensitivities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Combinations of FBGs and MZI (or MI), predominantly, provide opportunities for building of sensors for simultaneous sensing of temperature and RI. While there is a substantial number of different reported variations of RItemperature sensors that utilize MZI and FBG/LPFBG combinations, [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] mostly they share the same operational principle: MZIs are created by one of the methods described in Sec. 2.2 and are sensitive to both external RI variation and temperature, while FBGs are predominantly used as temperature sensing sections (in case of LPFBG, spectral features corresponding to LPFBG resonance also become RI-dependent, but this dependence is considerably lower than the spectral sensitivity of the modal interference caused by modes that are coupled by LPFBG into the cladding).…”
Section: Multiparameter Sensors Based On Combinations Of Fbg/lpfbgs Amentioning
confidence: 99%
“…Combinations of FBGs and MZI (or MI), predominantly, provide opportunities for building of sensors for simultaneous sensing of temperature and RI. While there is a substantial number of different reported variations of RItemperature sensors that utilize MZI and FBG/LPFBG combinations, [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] mostly they share the same operational principle: MZIs are created by one of the methods described in Sec. 2.2 and are sensitive to both external RI variation and temperature, while FBGs are predominantly used as temperature sensing sections (in case of LPFBG, spectral features corresponding to LPFBG resonance also become RI-dependent, but this dependence is considerably lower than the spectral sensitivity of the modal interference caused by modes that are coupled by LPFBG into the cladding).…”
Section: Multiparameter Sensors Based On Combinations Of Fbg/lpfbgs Amentioning
confidence: 99%
“…It can quickly absorb water molecules to form nanoscale molecular films of water [14]. The effective RI of the GO nano-film changes with the humidity of the surrounding environment, which will result in a change in spectral characteristics of an optical fiber interferometric sensor [15], [16], [17]. Several optical sensors based on the interaction between graphene and the evanescent wave of an optical waveguide have been proposed [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…With further research, many novel structures have been demonstrated, such as cascaded structure [6,7], core-offset structure [8], taper structure [9], fiber loop mirror with a section of special fiber [10], etc. Among above structures, a fiber loop mirror (FLM) or Sagnac interferometer is a very attractive method for use in optical fiber sensing due to its remarkable advantages, such as low cost, great flexibility and good stability [11].…”
Section: Introductionmentioning
confidence: 99%